Navigating uncertainty and negotiating trust in judicial deliberations - Bergman Blix, Stina; Törnqvist, Nina (Frontiers in Sociology, 2024)
Autonomy and independence are key features of legal decision-making. Yet, decision-making in court is fundamentally interactional and collective, both during the information gathering phase of hearings, and in evaluations during deliberations. Depending on legal system and type of court, deliberations can include different constellations of lay judges, jurors, or judge panels. In this article, we explore the collective dynamic of knowledge acquisition in legal decision-making, by analysing their emotional undercurrents. We show how judges balance uncertainty and certainty in legal deliberation, elaborating on (1) trust; (2) uncertainty exchange, and; (3) certainty as an agile emotion. Theoretically, the article combines an emotive-cognitive judicial framework, which understands emotion and reason as intersecting and continuous, with social interactionist theory. The analysis builds on extensive ethnographic fieldwork in Sweden, including shadowing and interviews with judges as well as observations during court proceedings and deliberations. The article actualizes the joint accomplishment of legal independence, and contributes with a nuanced account of how the decision-making process unfolds in legal deliberations.